PEMANFAATAN PROGRAM JAMINAN KESEHATAN NASIONAL DI PUSKESMAS DAERAH TERPENCIL KABUPATEN SUMBA TIMUR - Damaris Pura Tanya; Julita Hendrartini; Dwi Handono Sulistyo (Journal of Health Service Management, 2019)
Background: National Health Insurance has been performed since The implementation aims of performing National Health Insurance to facilitate access and utilization of health care. Public Health Center (PHC) as the forefront of health care and has major role to facilitate utilization of health care for members of National health Insurance. Nowadays, utilization of National Health Insurance in PHC has not reached national target amounts 15%. Objective: To explore determinant factors on utilization of national health insurance in remote PHC, East Sumba. Methods: The study type is qualitative with case study design. Variable included access of health care, health resources, medical needs and other factors. Amounts 20 informant involved this study. The informant included patient as members of National health Insurance, provider and head of district health office. Collecting data by indepth interview. Data analysis was conducted systematically by transcript, coding and analysis. Results: The higher utilization of national health insurance when traditional market was opened (market day). Limitation on access affected patient prefer to got services in outside. Limitation of health resources such as, unavailability of medicine and always exhausted, no lighting, and unavailability of water so utilization of PHC by patient was low. Most of patient need medical care in PHC such as need injection and unavailability of medicine so patient sought care out of PHC. Cultural factors still retained by society that diseases just be cured by a shaman. The pregnant women giving birth at home was high due to unavailability of waiting home (Rumah Tunggu) and village regulation has not examined about punishment of birth at home. Conclusion: Utilization of nasional health care in PHC remote area is less than optimal. It is not supported by adequate transportation facilities, the availability of drugs, and cultural changes.